Pemanfaatan Dana Bank Rakyat Indonesia (BRI) sebagai Sumber Pembiayaan Nelayan Gorontalo - Tiansi Febriani Idrus; Melizubaida Mahmud (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2020)
The research aims to find out the effetiviness of utilization of fund form BRI as fishermen’s financing source in Tanjung Kramat village,to find out supporting factors as well as inhibiting factors at people in Tanjung Kramat Village to achieve credit fund form Bank Rakyat Indonesia. The research method is a qualitative approach. The technique of data collection, interview and documentation. The findings show that the effectiviness ratio level is more than 100% and it means fund form Bank Rakyat Indonesia is very helpful for fishermen in Tanjung Kramat Village to increase the income. In addition, there are also two factors which support people in selecting fund form BRI as financing source namely internal and external factors. Also, there are also inhibiting factors namely credit instalment, credit value, collateral value, credit term, credit procedure/terms, credit provider allocation, and others.